Shared Understanding?Cross-Faculty Dialogue on the Challenges and Opportunities in the Emerging Focus on Spirituality - Janet Groen (Adult Education Research Conference, 2011)
This article presents the voices of six full-team faculty members in the faculties of education and social work within the Canadian university context who are interested in teaching courses that address an aspect of spirituality as part of the core content. Through our dialogue we had the opportunity to explore the hopes and the challenges of striving to be an undivided academic. We explored if and how our interest in integrating spirituality into our teaching practice emerged; how we understood spirituality and how this translated into our course content; and how spirituality was understood and valued by our respective students, faculties, universities and our disciplines.
Keywords: spirituality; higher education; dialogue